Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Anthony Ssebagereka; Rebecca Racheal Apolot; Evelyne Baelvina Nyachwo; Elizabeth Ekirapa-Kiracho (BMC, 2021)
Abstract Introduction This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service. Methods This costing analysis was done from the payer's perspective using the ingredients approach over five quarterly rounds of scoring between 2017 and 2018. Expenditure data was obtained from project records, entered and analyzed in Microsoft excel. Two scale-up scenarios, scenario one (considered cost inputs by the MakSPH research teams) and scenario two (considering cost inputs based on contextual knowledge from district implementing teams), were simulated to better understand the cost implications of integrating the Community Score Card (CSC) into a district health system. Results The total and average cost of implementing CSC for five quarterly rounds over a period of 18 months were USD 59,962 and USD 11,992 per round of scoring, respectively. Considering the six sub-counties (including one Town Council) in Kibuku district that were included in this analysis, the average cost of implementating the CSC in each sub-county was USD 1998 per scoring round. Scaling-up of the intervention across the entire district (included 22 sub-counties) under the first scenario would cost a total of USD 19,003 per scoring round. Under the second scaleup scenario, the cost would be lower at USD 7116. The total annual cost of scaling CSC in the entire district would be USD 76,012 under scenario one compared to USD 28,465 under scenario two. The main cost drivers identified were transportation costs, coordination and supervision costs, and technical support to supplement local implementers. Conclusion Our analysis suggests that it is financially feasible to implement and scale-up the CSC initiative, as an accountability tool for enhancing service delivery. However, the CSC design and approach needs to be embedded within local systems and implemented in collaboration with existing stakeholders so as to optimise costs. A comprehensive economic analysis of the costs associated with transportation, involvement of the district teams in coordination, supervision as well as provision of technical support is necessary to determine the cost-effectiveness of the CSC approach.